Comparison of small mammal prevalence of Leishmania (Leishmania) mexicana in five foci of cutaneous leishmaniasis in the State of Campeche, Mexico Comparación de las prevalencias de Leishmania (Leishmania) mexicana en mamíferos pequeños en cinco focos de leishmaniosis cutánea en el estado de Campeche, México - N.R. Van Wynsberghe; S.B. Canto-Lara; E.I. Sosa-Bibiano; N.A. Rivero-Cárdenas; F.J. Andrade-Narváez (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
In the Yucatan Peninsula of Mexico, 95% of the human cases of Cutaneous Leishmaniasis are caused by Leishmania (Leishmania) mexicana with an incidence rate of 5.08 per 100,000 inhabitants. Transmission is limited to the winter months (November to March). One study on wild rodents has incriminated Ototylomys phyllotis and Peromyscus yucatanicus as primary reservoirs of L. (L.) mexicana in the focus of La Libertad, Campeche. In the present study, the prevalence of both infection and disease caused by L. (L.) mexicana in small terrestrial mammals were documented during five transmission seasons (1994-2004) in five foci of Leishmaniasis in the state of Campeche. Foci separated by only 100 km, with similar relative abundances of small mammals, were found to differ significantly in their prevalence of both symptoms and infection. Transmission rates and reservoir species seemed to change in space as well as in time which limited the implementation of effective control measures of the disease even in a small endemic area such as the south of the Yucatan Peninsula. En la Península de Yucatán, México, la Leishmaniosis Cutánea es causada por Leishmania (L.) mexicana en 95% de los casos humanos, con una incidencia de 5.08% por cada 100,000 habitantes. El ciclo de transmisión se limita a la estación de invierno (noviembre- marzo). Un estudio de mamíferos silvestres incrimina a Ototylomys phyllotis y Peromyscus yucatanicus como reservorios primarios de L. (L.) mexicana en el foco de infección de La Libertad, Campeche. En el presente estudio, se documenta la prevalencia de infección/enfermedad causada por L. (L.) mexicana en pequeños mamíferos, durante cinco estaciones de transmisión (1994-2004) en cinco focos de CL del estado de Campeche. Los focos separados por solamente 100 km. de distancia, aún cuando tienen abundancias relativas de pequeños roedores similares, fueron significativamente diferentes en relación a la prevalencia de síntomas así como de infección. Las tasas de transmisión y las especies de reservorios parecen estar cambiando tanto en el tiempo como en el espacio, lo cual impide el establecimiento de adecuadas medidas de control de la enfermedad aún en un área endémica tan pequeña como lo es el sur de la Península de Yucatán.